“It's a very different world”: work transition and employability of higher education graduates - Monteiro, Sílvia Correia (2020)
Purpose: This study addresses the specific topic of transition between higher education and the world of work, taking differences naturally inherent to the individual and to the surrounding micro and macro contexts. With a holistic approach, this paper aimed to provide a deeper understanding about the university-to-work transition process in a period of turbulence and continuous changes in the labour market. Design/methodology/approach The three research questions that guide this qualitative study are as follows: (1) What are the factors that facilitate the transition to the labour market? (2) What are the factors that constrain the transition to the labour market? (3) What are graduates' perceptions of their employability? To answer these questions, eleven graduates were interviewed about facilitators and barriers of the transition process and perceptions of employability. Data collected from the interviews were then related to categories previously defined from the literature review. Version 12.0 of the NVivo software was used to support the process of data analysis. Findings Overall, participants' discourse refer to a multidimensional and dynamic perspective of factors related with work transition and employability. The obtained results indicate that the lack of career agency during graduation and professional experiences, together with late career exploration processes, represent possible barriers of transition, especially in study fields with targeted job offers. Likewise, experiences promoting the development of competencies through supportive practice from teachers, mentors and colleagues are referred as facilitators of transition. Practical implications One of the most consistent outcomes of the interviews conducted concerns the importance of a stronger focus on developing practical experiences during higher education studies. This empirical study demonstrated how this type of experience can mitigate the impact of the transition from university to the labour market. Originality/value This empirical study demonstrated how work being integrated into learning in curricula can mitigate the impact of the transition from university to the labour market. It offers important insights about possible strategies that could be adopted to promote graduates' employability from a perspective of shared responsibility.